ON b-ℊ-OPEN SETS - Indirani, K. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper, a new class of generalized open sets in a grill topological spaces called b-ℊ-open sets, is introduced and studied. This class is contained in the class of semi-pre-ℊ-open sets and contains all semi-ℊ-open sets and all pre-ℊ-open sets.